Smart indication system ( car park indication and reservation system - SmartPark ) - Ang, Calvin Wen Sen (2015)
Cars cruising around, searching for carpark spaces will cause harmful environmental impacts and unpleasant traffic build up particularly during peak hours in the urban areas. Traffic build up at entrances of carparks is a common sighting especially during peak hours and it will result into traffic inconveniences and contribute to negative environmental impacts. Presently, the Land Transport Authority (LTA) has various measures such as LED indication boards set up across the city to inform drivers of available car parking and Light Emitting Diode (LED) light indicator within the carpark as an indicator to guide drivers into available parking. However, drivers are still trapped in queues, spending too much time searching for car parking within the carpark premises as those indicators only assisted the drivers to avoid crowded places but failed to tackle the main concern which is to show drivers exactly on the location of the empty car parking space. SmartPark is an Android application that combines Wireless Sensor Networks (WSN) and mobile application development with the aim to inform and indicate to its user the next exact available parking space. WSN consist of various sensing components such as temperature, light, sound and etc. which are cost effective, low in maintenance and developed rapidly making it highly versatile. This application will also allow the user to pre-purchase empty spaces in advance to ensure space availability upon arrival. SmartPark will eliminate sourcing time for carpark spaces with push updates on the next available space while allowing drivers to pre-purchase their parking lots beforehand. Drivers will no longer need to cruise around and be trapped in traffic queues during the search for carpark spaces